Skenario dan Simulasi Target Indeks Pembangunan Manusia Lima Provinsi di Kalimantan 2024-2028 - Hayatun Nufus; Hidayatullah Muttaqin (PPJP ULM, 2026)
Unrealistic targets for the Human Development Index (HDI) often hinder the effectiveness of regional development planning. This study aims to formulate optimistic, moderate, and pessimistic HDI target scenarios for the 2024–2028 period across five provinces in Kalimantan, while simulating its constituent components: Mean Years of Schooling (MYS), Expected Years of Schooling (EYS), Life Expectancy (LE), and Adjusted Per Capita Expenditure (APE). Adopting a descriptive quantitative approach using Statistics Indonesia (BPS) data from 2010–2023, the data were analyzed through linear projection and average growth methods, processed via the Regional HDI Simulation Application. The findings indicate a consistent positive growth trend across all regions, with East Kalimantan projected to surpass a score of 80 by 2027. Adjusted Per Capita Expenditure (APE) is identified as the primary key driver for target achievement, in contrast to the education and health components, which exhibit stable but slower growth. The study recommends the necessity of economic transformation to enhance inclusive real income and the synchronization of optimistic scenarios into Regional Medium-Term Development Plans (RPJMD) to ensure the equitable sustainability of human quality of life in Kalimantan.